2021
DOI: 10.1101/2021.03.04.433859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scoping review of the applications of peptide microarrays on the fight against human infections

Arthur Vengesai,
Maritha Kasambala,
Hamlet Mutandadzi
et al.

Abstract: Introduction This scoping review explores the use of peptide microarrays in the fight against infectious diseases. The research domains explored included the use of peptide microarrays in the mapping of linear B-cell and T cell epitopes, antimicrobial peptide discovery, immunosignature characterisation and disease immunodiagnostics. This review also provides a short overview of peptide microarray synthesis.   Methods Electronic databases were systematically searched to identify relevant studies. The review w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…We previously reported that six methods can be used for the identification and prediction of linear B-cell epitopes (peptides) ( Vengesai et al, 2022 Jan ). For comprehensive mapping of B-cell epitopes, experimental techniques including overlapping peptides and phage display library are time consuming and expensive even for SARS-CoV-2 which has relatively few genes ( Vengesai et al, 2021 Mar 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that six methods can be used for the identification and prediction of linear B-cell epitopes (peptides) ( Vengesai et al, 2022 Jan ). For comprehensive mapping of B-cell epitopes, experimental techniques including overlapping peptides and phage display library are time consuming and expensive even for SARS-CoV-2 which has relatively few genes ( Vengesai et al, 2021 Mar 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that six methods can be used for the identification and prediction of linear B-cell epitopes (peptides) ( Vengesai et al, 2022 Jan ). For comprehensive mapping of B-cell epitopes, experimental techniques including overlapping peptides and phage display library are time consuming and expensive even for SARS-CoV-2 which has relatively few genes ( Vengesai et al, 2021 Mar 4 ). In contrast, in-silico B-cell epitope prediction bioinformatics techniques are manageable alternatives that allow for virtual cost-effective screening in the search for immuno-dominant epitopes with serological diagnostic potential ( Van Regenmortel, 1989 , 24 , Giacò et al, 2012 Jul 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation